STRATEGIC FOOD PRICE ELASTICITY IN EAST JAVA INDONESIA - Ana Arifatus Sa'diyah; Bahieddin Nofal; Umi Rofiatin; Aldon M. H. P. Sinaga (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Threats to food security have resulted in Indonesia frequently importing food products to meet domestic needs. Therefore elasticity of strategic food is important to study. The study results can be used as a reference for policy making in an effort to improve food security. The Study used a quantitative descriptive analysis method on Cross Section data from Susenas in March 2016. Analysis to identify household consumption preferences for food commodities (rice, corn, beef, shallots, chilies, and sugar) was performed using Microsoft Excel calculations. The analysis used to estimate the LA/AIDS model demand system is SUR. The results of the study show that the share of strategic food expenditure in East Java is strongly influenced by the price of the commodity itself, the price of other commodities and the amount of income in real terms, rice is the most preferred commodity compared to other commodities. Beef is still a luxury item that is relatively unaffordable by households in East Java. Rice is an elastic product according to Marshallian elasticity, but inelastic according to Hicksian elasticity. The Marshallian and Hicksian elasticity values are both negative, meaning that rice is a normal good. Rice price stability needs to be maintained so that household consumption is fulfilled. Given the negative elasticity of rice, which means when there is an increase in the price of rice, the demand for rice will decrease.